Peran Pendidikan Karakter dalam membentuk Kepribadian Siswa SMA di Era Digital - Sulistiyaningrum, Fitri (Universitas Tanjungpura, 2024)
This study aims to analyze the role of character education in shaping the personalities of high school students in the digital era, particularly concerning the use of technology in learning. Employing a qualitative descriptive method with a case study approach, the research involves 150 eleventh-grade students from three public schools in Pontianak. The research instruments include a questionnaire with 30 items measuring character values such as responsibility, integrity, and empathy; an interview guideline to obtain perspectives from students and teachers regarding the implementation of character education; and an observation sheet to record student behavior while using technology. Data were analyzed using thematic analysis techniques to identify patterns in student behavior. The findings indicate that technology-based character education enhances students' awareness of social responsibility and integrity. However, 40% of students reported difficulties in effectively controlling their use of technology, which negatively impacts self discipline. The study concludes that character education is highly relevant in the digital era but requires more integrated strategies and better supervision to mitigate the negative impacts of technology. Schools are advised to adopt a proactive approach to digital supervision and integrate character values into the curriculum.